Enhanced photocatalytic oxidation of reactive dye using manganese catalyst complex - Vajnhandl Simona; Škodič Lidija; Simonič Marjana; Lobnik Aleksandra; Volmajer-Valh Julija (Chemical Industry and Chemical Engineering Quarterly, 2022)
In this work, the treatment efficiency of advanced oxidation processes H2O2/UV enhanced by the addition of a manganese catalyst complex (MnTACN) was investigated on a model dye solution and a real dye-house effluent. The experimental results were evaluated in terms of absorbance (A) and total organic carbon (TOC) reduction. The major degradation products of the model dye solution were identified by high resolution gas chromatography/mass spectrometry analyses. In addition, the toxicity of the final reaction solution after H2O2/UV/MnTACN treatment to Vibrio fischeri bacteria was determined. The results showed that the addition of the H2O2/UV/MnTACN system at different concentrations of the catalyst solution increased the decolourisation rate compared to H2O2/UV for both the model dye solution and real dye-house effluent.